Biocomposite proton‐exchange membrane electrolytes for direct methanol fuel cells. Issue 25 (22nd March 2016) - Suganthi, S; Mohanapriya, S; Raj, V.
ABSTRACT: Poly(vinyl alcohol) (PVA)‐amino acid (AA) biocomposite membranes are prepared by blending PVA with AAs such as glycine, lysine (LY), and phenyl alanine followed by in situ crosslinking with citric acid (CA) and explored as a new class of biocomposite membrane electrolytes for direct methanol fuel cells (DMFCs). CA crosslinks with PVA through esterification offers adequate chemical, thermal, and morphological stability thereby produces methanol‐obstructing close‐packed polymeric network. These biocomposite membranes are characterized in terms of mechanical, thermal, sorption, and proton‐conducting properties. Hydrophilic nature of AA zwitterions significantly facilitates proton conduction and CA crosslinking mitigates methanol crossover through establishing appropriate balance between hydrophilic/hydrophobic domains. The rational design of membrane microstructure with proper arrangement of hydrophobic/hydrophilic domains is a key to enhance electrochemical selectivity of PVA‐AA/CA biocomposite membranes. Biocomposite membrane comprising LY exhibits nearly threefold higher electrochemical selectivity in relation to PVA/CA blend membrane. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43514. Abstract :